Case study of uncontrolled diabetes mellitus with neurodermatitis, peripheral neuropathy, and obesity type i with central obesity - Difania Leovanka Onko; Clement Drew; Paras Risart Azzahra; Justina (Science Midwifery, 2023)
Diabetes Mellitus (DM) is a metabolic disease caused by abnormalities in the secretion of insulin, and the action of insulin, or both of them. In 2019, The International Diabetes Federation organization estimates 463 million people in the world who suffer from DM and Southeast Asia ranked third at 11.3%. While Indonesia is ranked 7th in Southeast Asia with 10.7 million patients. The prevalence of DM increased from 6% in 2013 to 8.5% in 2018. Based on Riskesdas 2018, DM disease in Banten province is amount of 1.62% (23,262). In 2021, there were 146 cases at Legok Public Health Center continuing to increase. Controlled blood sugar and risk factors for Diabetes Mellitus were conducted in Mr. F so that the complications could be prevented. Family medicine approaches with the Mandala of Health paradigm in a 49-year-old man was used for the complaints of wounds in both legs, itching since 2 years ago, headaches, fatigue, and tingling in the legs suffering from DM since November 2021. Based on the anamnesis of physical and supporting examination, the patient was diagnosed with uncontrolled DM accompanied by peripheral neuropathy, central obesity, and neurodermatitis potential diabetic ulcer. The results of the intervention showed a decrease in blood sugar, weight loss of 2 kg, complaints of itching, tingling, and wounds on both legs improved in Mr. F. Risk factors for uncontrolled blood sugar in Mr. F involved lack of knowledge, unhealthy lifestyle, lack of physical activity, non–compliance with medication and, doing control to the Health Center, financial limitations, as well as lack of support from Mr. F's family.